Transforming Island Community-Based Village Governance: A Strategy for Sustainable Development in Ternate - Muhlis Hafel; Julfi Jamil; Roman Hadi Saputro (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study evaluates the urgency of transforming the administrative status of urban villages on Hiri Island, Ternate City, to village status as a strategy to strengthen local governance and promote tourism-based village development in island regions. The research is driven by persistent development disparities across island areas, the limitations of the urban-administrative governance model for urban villages, and the restricted fiscal capacity of urban villages to support local development. The communal and customary social characteristics of the Hiri Island community are considered more compatible with the participatory governance model for villages. This research uses a qualitative case study design across six urban villages in Hiri District. Data collection methods included interviews, observations, and documentation involving government officials, traditional leaders, local communities, and tourism stakeholders. Data analysis was performed using source and method triangulation. The findings demonstrate that transforming to desa status can enhance community participation in development, reinforce the legitimacy of local leadership, and facilitate the integration of customary institutions with formal governance systems. Access to village funds further enables increased financing for infrastructure, public services, economic empowerment, and the development of community-based tourism villages. Nevertheless, implementation continues to face challenges, including inadequate infrastructure, limited human resource capacity, weak tourism institutions, and suboptimal environmental management. The study recommends the formulation of adaptive regulations; capacity-building initiatives for government officials and local communities; infrastructure development and improved inter-island connectivity; and the promotion of multi-stakeholder collaboration to support participatory and sustainable development in island regions.